Almost periodic dynamics in a new class of impulsive reaction–diffusion neural networks with fractional-like derivatives. (February 2021) - Stamov, Gani; Stamova, Ivanka; Martynyuk, Anatoliy; Stamov, Trayan
Abstract: This paper introduces a new class of reaction–diffusion neural networks with impulses and recently defined fractional-like derivatives. Sufficient conditions for the existence-uniqueness of almost periodic solutions are proposed by constructing suitable Lyapunov-like functions. Our results are new and contribute to the development of the knowledge on impulsive fractional-like evolution models. Finally, as an example a fractional-like generalization of a reaction-diffusion model in epidemiology that simulates the hepatitis B virus (HBV) infection with spatial dependence is considered.